2021
DOI: 10.1007/s12063-021-00199-8
|View full text |Cite
|
Sign up to set email alerts
|

Thirteen years of Operations Management Research (OMR) journal: a bibliometric analysis and future research directions

Abstract: The journal of Operations Management Research (OMR) is a rigorous journal that started its publication in 2008. It publishes short, focused research studies that advance both the theory and practice of operations management. Considering the relevant OMR's contribution to the field of Operations Management in the last years, this study provides an overall assessment of the journal performance by conducting a retrospective review. To elaborate on OMR's temporal development in terms of publications, authors, affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…While keywords cooccurrence indicates the number of publications in which both the keywords/terms appear together. In other terms, coauthorship measures the degree of connectivity among the coauthors affiliated to one or different institutions (Peters & Van Raan, 1991), while cooccurrence of the keywords reveals the existing literature's conceptual structure (Ravikumar et al, 2015;Callon et al, 1983;Dhiaf et al, 2021;Sharaf, 2021;Abu Nassar and Al Twerqi, 2021) as frequent coappearance of words in different documents disclose their thematic relationship (Callon et al, 1983) and [Colour figure can be viewed at wileyonlinelibrary.com] analysis of the content of such a document enables a researcher to conceptualize the field (Andersen, 2019;Aminova et al, 2020). Moreover, the study uses quantitative indicators to depict the bibliographic data, such as the total number of articles and citationss to measure productivity and impact, respectively, and other metrics such as average citation per article that combines both publications and citations.…”
Section: Methodology and Datasetmentioning
confidence: 99%
“…While keywords cooccurrence indicates the number of publications in which both the keywords/terms appear together. In other terms, coauthorship measures the degree of connectivity among the coauthors affiliated to one or different institutions (Peters & Van Raan, 1991), while cooccurrence of the keywords reveals the existing literature's conceptual structure (Ravikumar et al, 2015;Callon et al, 1983;Dhiaf et al, 2021;Sharaf, 2021;Abu Nassar and Al Twerqi, 2021) as frequent coappearance of words in different documents disclose their thematic relationship (Callon et al, 1983) and [Colour figure can be viewed at wileyonlinelibrary.com] analysis of the content of such a document enables a researcher to conceptualize the field (Andersen, 2019;Aminova et al, 2020). Moreover, the study uses quantitative indicators to depict the bibliographic data, such as the total number of articles and citationss to measure productivity and impact, respectively, and other metrics such as average citation per article that combines both publications and citations.…”
Section: Methodology and Datasetmentioning
confidence: 99%
“…The top ten authors are initially reported on the basis of h-index, total citations, and total publications, as shown in Table 7. The h-index (h) denotes that a researcher has h articles that have been cited at least h times, and is an indicator of both productivity and citation impact (Dhiaf et al, 2021). From the table, Ramanathan R has played the most pivotal role in the field by focusing on the effects of different ERs, environmental pressures, and organizational stresses on environmental performance, respectively (R. Li and Ramanathan, 2018;Ramanathan et al, 2014;Yu et al, 2017).…”
Section: Top Authors and Relevant Affiliationsmentioning
confidence: 99%
“…The analytical representation of the keywords played a significant role to give an interrelatedness of the research in the given field (Su and Lee, 2010). The outcome of the keywords assists the researchers to choose their keywords for upcoming research work which helps them to develop cognitive understanding through the co-occurrence visualisation (Dhiaf et al , 2021).…”
Section: Analysis Of Bibliometric Visualisationmentioning
confidence: 99%